PEMANFAATAN MEDIA BELAJAR BERBASIS LINGKUNGAN UNTUK MENINGKATKAN KEMAMPUAN SISWA MENULIS TEKS BERBENTUK GREETING CARD - Hastutik, Wiji (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
The students’ability of class IX.1 SMPN 7 Muara Bungo in writing greeting card is still low. This research is aimed to describe the using of environment sources as teaching media or mebelbasling in improving the students’writing ablity. This research is included i classroom action research with 32 students as the research subjects. This research was implemented in two cycles and each cycle consist of planning, doing, observing and reflecting. The instrument in data collecting used observation sheet, test and field note. The result showed that (1)The using of environment sources as teaching media was able to improve the student’ ability in writing greeting cardeither in content, grammar, coherence as well as the tidy. (2) The using of environment sources as teaching media was able to increasethe student’s completeness in wring english text. It’s indicated from the increasing of test result 0,5% in the first cycle and 3,08% in the second cycle.